Azole sensitivity in Leptosphaeria pathogens of oilseed rape: the role of lanosterol 14α-demethylase. Issue 1 (December 2017) - Sewell, Thomas; Hawkins, Nichola; Stotz, Henrik; Huang, YongJu; Kelly, Steven; Kelly, Diane; Fraaije, Bart; Fitt, Bruce
Abstract Lanosterol 14-α demethylase is a key enzyme intermediating the biosynthesis of ergosterol in fungi, and the target of azole fungicides. Studies have suggested thatLeptosphaeria maculans andL. biglobosa, the causal agents of phoma stem canker on oilseed rape, differ in their sensitivity to some azoles, which could be driving pathogen frequency change in crops. Here we used CYP51 protein modelling and heterologous expression to determine whether there are interspecific differences at the target-site level. Moreover, we provide an example of intrinsic sensitivity differences exhibited by bothLeptosphaeria spp.in vitro andin planta . Comparison of homologous protein models identified highly conserved residues, particularly at the azole binding site, and heterologous expression of LmCYP51B and LbCYP51B, with fungicide sensitivity testing of the transformants, suggests that both proteins are similarly sensitive to azole fungicides flusilazole, prothioconazole-desthio and tebuconazole. Fungicide sensitivity testing on isolates shows that they sometimes have a minor difference in sensitivityin vitro andin planta . These results suggest that azole fungicides remain a useful component of integrated phoma stem canker control in the UK due to their effectiveness on bothLeptosphaeria spp. Other factors, such as varietal resistance or climate, may be driving observed frequency changes between species.